1993
DOI: 10.1016/0014-5793(93)80030-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid oxidation on glucose utilization by isolated hepatocytes

Abstract: We have studied the inhibitory action of long-and short-chain fatty acids on hepatic glucose utilization in hepatocytes isolated from fasted rats. The rates of hepatic glucose phosphorylation and glycolysis were determined from the tritiated products of [2-'H] and [6-3H]glucose metabolism, respectively. The difference between these was taken as an estimate of the 'cycling' between glucose and glucose-6-phosphate. In the presence of 40 mM glucose this cycling was estimated at 0.68 pmol/min/g wet wt. Glucose pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Furthermore, overexpression of glucose transporter Slc2a1 in mouse cardiac tissue increases glucose uptake and oxidation while decreasing FAO, despite a high supply of fatty acids (Yan et al 2009). A relationship between FAO and glucose consumption and oxidation has also been reported in rat hepatocytes (Berry et al 1993), rat myocytes (Abdel-aleem et al 1994), rat skeletal muscle (Kaushik et al 2001), and rat (Saddik et al 1993, Lavrentyev et al 2004) and mouse cardiac tissues (Campbell et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, overexpression of glucose transporter Slc2a1 in mouse cardiac tissue increases glucose uptake and oxidation while decreasing FAO, despite a high supply of fatty acids (Yan et al 2009). A relationship between FAO and glucose consumption and oxidation has also been reported in rat hepatocytes (Berry et al 1993), rat myocytes (Abdel-aleem et al 1994), rat skeletal muscle (Kaushik et al 2001), and rat (Saddik et al 1993, Lavrentyev et al 2004) and mouse cardiac tissues (Campbell et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In hepatocytes of both normal and diabetic rats, glucose cycling between glucose and G6P was elevated when glycolysis was suppressed by an increase in fatty acids in the media (32)(33)(34) and the elevation of glucose cycling was associated with an increased flux through glucose 6-phosphatase (33). Lipid infusion rapidly increased hepatic glucose 6-phosphatase gene expression and protein content in rats (35).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our current and previous (38,39) data confirm that suppression of plasma NEFA concentrations shifts the liver into a more glycolytic mode. In vitro evidence has shown that glycolysis is inhibited in isolated hepatocytes incubated with fatty acids (32,40). The shift toward glycolysis when fatty acid levels are low could result from a fall in citrate, one of the major inhibitors of phosphofructokinase, the first rate-determining enzyme in the glycolytic pathway (32,40).…”
Section: Discussionmentioning
confidence: 99%
“…The other major radioactive products of glucose and lactate metabolism (glucose, lactate, pyruvate, amino acids and water) were resolved by ion-exchange chromatography [7,211. Isotopic glycogen formation was measured as previously described [22].…”
Section: Methodsmentioning
confidence: 99%